Receptor tyrosine kinase (RTK) targeting in pediatric high-grade glioma and diffuse midline glioma: Pre-clinical models and precision medicine - Schwark, Kallen; Messinger, Dana; Cummings, Jessica R.; Bradin, Joshua; Kawakibi, Abed; Babila, Clarissa M.; Lyons, Samantha; Ji, Sunjong; Cartaxo, Rodrigo T.; Kong, Seongbae; Cantor, Evan; Koschmann, Carl; et al. (Frontiers in Oncology, 2022)
Pediatric high-grade glioma (pHGG), including both diffuse midline glioma (DMG) and non-midline tumors (both henceforth referred to as “pHGG”), continues to be one of the deadliest oncologic diagnoses. Targeted therapy options aimed at key oncogenic receptor tyrosine kinase (RTK) drivers using small-molecule RTK inhibitors has been extensively studied, but the absence of proper in vivo modeling that recapitulate pHGG biology has historically been a research challenge. Thankfully, there have been many recent advances in animal modeling, including Cre-inducible transgenic models as well as intra-uterine electroporation (IUE) models, which closely recapitulate the salient features of human pHGG tumors. Over 20% of pHGG have been found in sequencing studies to have alterations in platelet derived growth factor-alpha (PDGFRA), making growth factor modeling and inhibition via targeted tyrosine kinases a rich vein of interest. With commonly found alterations in other growth factors, including FGFR, EGFR, VEGFR as well as RET, MET, and ALK, it is necessary to model those receptors, as well. Here we review the recent advances in murine modeling and precision targeting of the most important RTKs in their clinical context. We additionally provide a review of current work in the field with several small molecule RTK inhibitors used in pre-clinical or clinical settings for treatment of pHGG.